Emotional education in the COVID-19 pandemic context - Cruz Xiomara Peraza de Aparicio (Medisur)
In pandemic times, it is important that people develop social-emotional learning skills in order to deal with stressful situations, and that these are approached with calmness and balanced emotional responses. The objective of this article is to reflect on the role of emotional education in pandemic conditions. Current trends advocate its insertion into teaching curricula, including introducing it as a new vision of the world, with a view to physical and mental well-being. Today, it represents a challenge for all of humanity, in order to strengthen the capacity to face adversity with more resilient positions. It can only be effective from an emotional balance and adequate mental health of the social actors involved.